An Exploration of Indonesian Accounting Education Practices - Ika Rahmawati; Ani Wilujeng Suryani (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2021)
This study reviewed the development of accounting education research in Indonesia for 21 years. The reviews were conducted on 428 accounting education articles in the nationally accredited journals from 1999 to 2019. A bibliometric approach and content analysis were used to analyze the articles’ topics, theories, methods, and characteristics. This study also separated the period of 21 years into two decades. The results show that accounting education research topics revolved on curriculum and teaching, content-based teaching, educational technology, students and faculty dominated by many quantitative studies. T-test, regression, and path analysis were the most commonly used data analysis techniques. However, only 86 articles framed the studies with the common behavioral, motivational, and fraud theories. Interestingly, some articles used the “gone theory” which actually never existed. Based on the topic classifications, "students" were the most frequently discussed subjects, followed by the content-based teaching, curriculum and teaching, and lastly teaching staff and educational technology. The results of this study suggest that more studies on accounting curriculum should be conducted emphasizing on technology for the accounting education 4.0.